Distribution of Corbicula fluminea (Muller, 1774) in the invaded range: a geographic approach with notes on species traits variability - Crespo, Daniel
Corbicula fluminea is considered one of the most important non-native invasive species (NIS) in aquatic systems mainly due to its widespread distribution and ecological and economic impacts. This species is known to negatively affect native bivalves, also with severe effects on biodiversity and ecosystem functioning. Throughout an exhaustive bibliographic survey and with the aid of Geographic Information Systems tools, this study tracks the species dispersion from its native range, including the description of important physical and environmental barriers. Additional analyses were conducted to examine possible influences of latitudinal/ temperature gradients on important traits (e.g. life span, maximum and mean body length, growth at the end of first year). Altitude and winter minimum temperature appear to be delaying the invasion worldwide, but it seems inevitable that the species will spread across the globe. Latitude and summer temperature show a relationship with growth and life span. Overall, the information gathered in this review may be relevant to forecast future distribution patterns of this NIS, and to anticipate the possible implementation of effective management measures. Moreover, it may constitute a valuable tool in the prediction of population responses to an increasingly changing environment.